2007
DOI: 10.1107/s1600536807009543
|View full text |Cite
|
Sign up to set email alerts
|

2,6-Bis({rac-1-[2-(diphenylphosphino)ferrocenyl]ethyl}aminocarbonyl)pyridine

Abstract: The title compound, [Fe2(C21H21N3O2)(C17H14P)2], a new potential penta­dentate ligand with (non‐crystallographic) C2 axial symmetry, shows intra­molecular π–π inter­actions and weak C—H⋯O hydrogen bonds in the crystal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…A search of the Cambridge Structural Database (Version 5.37; last update March 2016; Groom et al, 2016) for structures of molecules containing an analogous tridentate ferrocene PNP scaffold revealed no entries. However, three molecules where the secondary amine functionality is replaced by a longer linker were found: AZAHED (amine substituted for imidazolium; Gischig & Togni, 2005), ALEZMOS (2,6-pyridine dicarboxamide; Reddy et al, 2007) and PEDTEX (piperazine; Zhou & Zhang, 2005). Finally, in XARUD (You et al, 2000) the amine functionality is substituted by a cyclohexanediamine unit.…”
Section: Database Surveymentioning
confidence: 99%
“…A search of the Cambridge Structural Database (Version 5.37; last update March 2016; Groom et al, 2016) for structures of molecules containing an analogous tridentate ferrocene PNP scaffold revealed no entries. However, three molecules where the secondary amine functionality is replaced by a longer linker were found: AZAHED (amine substituted for imidazolium; Gischig & Togni, 2005), ALEZMOS (2,6-pyridine dicarboxamide; Reddy et al, 2007) and PEDTEX (piperazine; Zhou & Zhang, 2005). Finally, in XARUD (You et al, 2000) the amine functionality is substituted by a cyclohexanediamine unit.…”
Section: Database Surveymentioning
confidence: 99%
“…In fact, some of them are copper-selective. We have recently prepared and reported the crystal structure of a bis(ferrocenyl)pyridyl amide (Scheme 1) [7]. In addition, we prepared the phenyl analogue of this ligand for comparative reactivity studies, as shown in Scheme 1.…”
mentioning
confidence: 99%